ENERGY-EFFICIENT WASTEWATER TREATMENT: DESIGN AND EVALUATION OF UASBR-ASP SYSTEM FOR BIOGAS GENERATION AND CO₂ MITIGATION - Amit Kumar Tiwari, Vijay Kumar Upadhyay, Arun Kumar Agarwal; Tripuresh Joshi (Chelonian Research Foundation, 2025)
This paper is about the process description and design both for Up flow Anaerobic Sludge Blanket Reactor (UASBR) followed by Activated Sludge Process (ASP) for the treatment of wastewater of potato processing industry. The estimation of biogas generation reveals CO2 emission reduction under scope 1 by replacing piped natural gas (PNG) uses in boiler and electricity reduction under scope 2 by reducing the organic load to ASP after UASBR, resulting in lower oxygen demand which was expected to be supplied by surface aerators. The design detail states that removing 9000 kg COD/day in UASBR with 90% efficiency will reduce the load on ASP resulting reduction of approximately theoretical oxygen demand of 9000 kg of oxygen excluding quantity of oxygen requirement for amonical nitrogen. The estimation of biogas will help further to estimate the CO2 emission reduction at plant scale. Hence wastewater treatment through UASBR followed by small polishing unit ASP will help in reducing CO2 emissions under scope 1 and scope 2 both with concept of waste to energy, waste to economy for sustainable development.